2022
DOI: 10.1590/fst.50821
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tea polyphenols and EGCG on glucose metabolism and intestinal flora in diabetic mice fed a cornstarch-based functional diet

Abstract: One-month-old Female Kunming mice (body weight 20±3 g) was provided by the Animal Experiment Center, Zhejiang Academy of Medical Sciences (Hangzhou, China). Basal feed was purchased from Jiangsu Collaborative Bioengineering co.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The relative abundance of Prevotellaceae in RS group and H-RR group was 13.96-14.74, while that in the other three groups was only 1.50-3.92. The abundance of Prevotellaceae in normal rats' intestinal flora was significantly higher than that of non-normal rats (Liu et al, 2022), indicating that recombinant rice could effectively restore rats' disordered intestinal flora.…”
Section: The Difference Of Intestinal Flora Distribution At the Level...mentioning
confidence: 90%
“…The relative abundance of Prevotellaceae in RS group and H-RR group was 13.96-14.74, while that in the other three groups was only 1.50-3.92. The abundance of Prevotellaceae in normal rats' intestinal flora was significantly higher than that of non-normal rats (Liu et al, 2022), indicating that recombinant rice could effectively restore rats' disordered intestinal flora.…”
Section: The Difference Of Intestinal Flora Distribution At the Level...mentioning
confidence: 90%
“…In turn, Han et al [ 169 ] demonstrated that yellow tea, the least popular variety worldwide, has the strongest anti-hyperglycemic effects. Diabetic mice receiving a functional diet composed of corn-starch supplemented with tea polyphenols and EGCG showed a decreased fasting level of blood glucose as compared to mice not receiving polyphenols or EGCG; they also showed an improvement in terms of the intestinal microbiota profile [ 170 ]. Similar results were observed in diabetic rats receiving green tea enriched with catechin and inulin [ 171 ].…”
Section: Anti-obesogenic Antidiabetic and Antioxidative Properties Of...mentioning
confidence: 99%
“…Functional ingredients in tea has many function actions, including reducing resistance to insulin (Lin and Lin, 2008) inhibiting lipid absorption (Nakai et al, 2005), and enhancing fat oxidation (Sae-tan et al, 2011) . Most importantly, studies have shown that tea could positively modify the intestinal flora (Thomas et al, 2010), and it play a role in protecting against diabetes (Ribaldo et al, 2009) by reversing and promoting the ecological balance of intestinal flora (Zhang et al, 2020;Liu et al, 2022). Matcha is one kind of tea resources, and is loved by young consumers because of its application in food.…”
Section: An Exploratory To Analysis the Effects Of The Dirrerent Role...mentioning
confidence: 99%